2021
DOI: 10.1177/00472875211028313
|View full text |Cite
|
Sign up to set email alerts
|

Living the Experience Before You Go . . . but Did It Meet Expectations? The Role of Virtual Reality during Hotel Bookings

Abstract: Virtual reality (VR) is considered an important technological development to impact the tourism industry. Hotels are constantly attempting to overcome the challenges they face in the presentation of their facilities in the virtual environment. This research has made one of the first attempts to understand VR’s ability to influence tourism consumers’ attitudes and behavioral intentions during the prepurchase phase and postpurchase phase of their purchase journey across three hotel preview styles, namely, (1) VR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 76 publications
4
45
0
Order By: Relevance
“…Israel et al (2019) found that using a smartphone-based virtual reality system had a positive effect on visit intentions. Similarly, McLean and Barhorst (2021) found that both HMD-based VR and 360° tour-based VR had greater influence than static images on visit intention. Therefore, the following hypothesis is proposed:…”
Section: Dimensions Of Technological Acceptance and Visit Intention A...mentioning
confidence: 88%
“…Israel et al (2019) found that using a smartphone-based virtual reality system had a positive effect on visit intentions. Similarly, McLean and Barhorst (2021) found that both HMD-based VR and 360° tour-based VR had greater influence than static images on visit intention. Therefore, the following hypothesis is proposed:…”
Section: Dimensions Of Technological Acceptance and Visit Intention A...mentioning
confidence: 88%
“…The advertising studies in tourism explored advertising using social media, YouTube and video streaming (Alamäki et al , 2019; Hoi, 2020; Moliner-Velázquez et al , 2022; Stafford, 2020) and virtual reality (Lyu et al , 2021; McLean and Barhorst, 2022). This online advertising and information creates confusion in consumers' minds and affects the consumers' decisions (Sharma et al , 2022) related to visiting or booking intentions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the research also explores the effect of online reviews (Shukla and Mishra, 2022; Wen et al , 2021) and e-word-of-mouth (Moliner-Velázquez et al , 2022) on hotel booking intention. The extant studies also reveal the effect of virtual reality on hotel booking intention (Lyu et al , 2021; McLean and Barhorst, 2022).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…However, immersive VR headsets are used in the hotel sector, where online preview is more developed. Despite their availability, McLean and Barhorst (2022) demonstrated no difference between immersive VR headsets and 360-degree real panorama VR regarding consumer learning and hotel visit intentions. Future research can explore the possibility of immersive VR headset applications in the online preview of P2P accommodation and test whether there is a difference between immersive VR headsets and 360-degree panorama VR usage in the P2P accommodation sector.…”
Section: Limitations and Future Research Suggestionsmentioning
confidence: 92%
“…In online reservation contexts, consumer booking decisions typically rely more on cognitive appraisal to reduce booking risk (Kim, Lee, & Jung, 2020). Moreover, consumer reservation behaviors are at the pre-purchase stage of the customer journey, meaning that consumers have not yet truly experienced P2P accommodation services, and there may be no apparent emotional response due to a service experience (McLean & Barhorst, 2022). Therefore, we followed previous research and used only cognitive appraisal in its research model (Claffey & Brady, 2017, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%